PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI MOMENTUM DAN IMPULS KELAS X SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: The learning device develope are learning device based on the Problem Based Learning model on momentum and impulse material for class X high school students, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Learning Result Test. The purpose of this study was to determine the validity of learning device based on the Problem Based Learning model on momentum and impulse material. This type of research is a Research and Development (R&D) with a 4D model design. The research instrument used was the RPP validation assesment sheets, LKPD , and Leraning Result Test which were used by the validator to asses learning device. Data analysis in this study used desciptive analysis, by calculating the validity score of each indicator of the learning device. Based on the Results of the validity data analysis, the average value of the validity of the lesson plans for the first meeting was 3,48 with a very high category, the average validity value of the validity of the lesson plans for the second meeting was 3,57 with a very high category, and the average validity value of the validity of the lesson plans for the third meeting was 3,54 with a very high category. The average validity of LKPD 01 was 3,61 with a very high category, the average validity of LKPD 02 was 3,33 with a very high category, and the average validity of LKPD 03 was 3,64 with a very high category. The average validity of the Learning Result Test was 3,57 with a very high category, so that the overall average learning device was 3,53 with a very high category. Thus learning device based on the Problem Based Learning models is declared valid and the suitable for use in momentum and impulse material in class X SMA.Key Words: Physics Learning Device, Problem Based Learning Models, Momentum and Impuls